2020
DOI: 10.1038/s41598-020-77228-2
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcome and prognostic factors in anaplastic oligodendroglioma: a single-institution study of 95 cases

Abstract: The aim of this study was to evaluate prognostic factors including surgical, radiographic, and histopathologic analyses in anaplastic oligodendroglioma (AO) patients. We reviewed the electronic records of 95 patients who underwent surgery and were diagnosed with AO for 20 years. The primary endpoints were progression-free survival (PFS) and overall survival (OS). Univariate and multivariable analyses included clinical, histopathological, and radiographic prognostic factors. Subgroup analysis was performed in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
5
10
0
Order By: Relevance
“…Ability to achieve gross total resection, which is often easier in the frontal lobe, could also contribute to differences in clinical outcome. 49 , 50 Survival outcomes of the LCN groups roughly reflect previously reported survival outcomes stratified by molecular genetic subtyping, wherein IDH-wt, IDH-mut/1p19q non-codeleted and IDH-mut/1p19q non-codeleted tumours rank in the order of lowest to highest in median overall survival. 36 LCN groups did not relate significantly with survival outcome when the cohort was stratified into GBM-only and LGG-only cases ( Supplementary Table 1 ).…”
Section: Resultssupporting
confidence: 75%
“…Ability to achieve gross total resection, which is often easier in the frontal lobe, could also contribute to differences in clinical outcome. 49 , 50 Survival outcomes of the LCN groups roughly reflect previously reported survival outcomes stratified by molecular genetic subtyping, wherein IDH-wt, IDH-mut/1p19q non-codeleted and IDH-mut/1p19q non-codeleted tumours rank in the order of lowest to highest in median overall survival. 36 LCN groups did not relate significantly with survival outcome when the cohort was stratified into GBM-only and LGG-only cases ( Supplementary Table 1 ).…”
Section: Resultssupporting
confidence: 75%
“…The prognosis for anaplastic glioma remains poor despite combination treatment with surgery, RT, and CT [6]. In our cohort,48.13% of patients with anaplastic glioma underwent complete resection, and our ndings were consistent with those of previous studies, in which the percentage ranged from 30-60% in different reported cohorts [5,17,18]. Randomized controlled trials (RCTs) have shown that patients with anaplastic glioma are more likely to bene t from postoperative adjuvant treatment [19,20].…”
Section: Discussionsupporting
confidence: 90%
“…Most studies have reported the overall survival (OS) and predictors of survival in the anaplastic glioma population, of which several have revealed that surgery is associated with improved survival in WHO grade III gliomas [5][6][7][8]. The extent of resection for anaplastic gliomas has not been associated with survival [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, surgeons should biopsy patients suspected to have AO and attempt tumor resection, as with all other highgrade gliomas. In a study by Shin et al (2020), gross tumor resection (GTR) was done in 43 of 88 patients. Upon multivariate analysis, median progression free survival (PFS) was 41.1 vs. 23.9 months along with a hazard ratio (HR) of 0.58 with a 95% CI 0.35-0.97 (p = 0.038) compared to patients who had no GTR (Shin et al, 2020).…”
Section: Current Management Guidelinesmentioning
confidence: 99%
“…In a study by Shin et al (2020), gross tumor resection (GTR) was done in 43 of 88 patients. Upon multivariate analysis, median progression free survival (PFS) was 41.1 vs. 23.9 months along with a hazard ratio (HR) of 0.58 with a 95% CI 0.35-0.97 (p = 0.038) compared to patients who had no GTR (Shin et al, 2020). However, upon multivariate analysis there was no significant difference in overall survival (OS).…”
Section: Current Management Guidelinesmentioning
confidence: 99%